1999
DOI: 10.1081/ddc-100102211
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rapidly Disintegrating Tablets Prepared by a Direct Compression Method

Abstract: To make rapidly disintegrating tablets with sufficient mechanical integrity as well as a pleasant taste, microcrystalline cellulose (MCC), Tablettose (TT), and crosslinked sodium carboxymethyl cellulose (Ac-di-sol) or erythritol (ET) were formulated. Tablets were made by a direct compression method (I). Tablet properties such as porosity, tensile strength, and disintegration time were determined. The tensile strength and disintegration time were selected as response variables, tablet porosity and parameters re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
113
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(124 citation statements)
references
References 7 publications
5
113
1
Order By: Relevance
“…Bi et al, 1999 reported that for 8 mm tablets, a 5-fold increase in the CF to 4.9 kN caused approximately an 11-fold increase in the tensile strength to 23 kg/cm 2 and a 2.4-fold increase in DT of tablets to 31 s. 75…”
Section: Introductionmentioning
confidence: 99%
“…Bi et al, 1999 reported that for 8 mm tablets, a 5-fold increase in the CF to 4.9 kN caused approximately an 11-fold increase in the tensile strength to 23 kg/cm 2 and a 2.4-fold increase in DT of tablets to 31 s. 75…”
Section: Introductionmentioning
confidence: 99%
“…Paediatrics and geriatric patients, due to the physiological changes shows difficulty in swallowing which is a common problem associated with these groups. Improvement of a Mouth melt tablet a novel type of solid dosage form may reduce difficulty in swallowing, since they show faster disintegration and melts rapidly in saliva without the need of drinking water where the tablet disperses rapidly in the mouth before it is swallowed (Bi et al, 1996;Bi et al, 1999). Orodispersible tablets, fast dissolving tablets, melt-in-mouth tablets, rapid melts, porous tablets and quick dissolving tablets were categorized under mouth dissolving tablets (Sreenivas et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The difference in the weight is noted and is expressed in percentage. It 14 should be preferably between 0.5 to 1.0%.…”
Section: Friabilitymentioning
confidence: 99%